2015
DOI: 10.1902/jop.2014.140539
|View full text |Cite
|
Sign up to set email alerts
|

Bruxism Is Unlikely to Cause Damage to the Periodontium: Findings From a Systematic Literature Assessment

Abstract: Despite the scarce quantity and quality of the literature that prevents sound conclusions on the causal link between bruxism and the periodontal problems assessed in this review, it seems reasonable to suggest that bruxism cannot cause periodontal damage per se. It is also important to emphasize, however, that because of methodologic problems, particularly regarding sleep bruxism assessment, more high-quality studies (e.g., randomized controlled trials) are needed to further clarify this issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 35 publications
(110 reference statements)
1
31
0
3
Order By: Relevance
“…While the advantages of this approach may be intuitive to researchers involved in the field, it must be pointed out that it may also influence the future construct of bruxism. For years, bruxism has been generically called into cause as a risk factor for several clinical consequences of dental interest, but the literature has always failed to show a clear‐cut relationship with the purported effects, such as TMDs, occlusal trauma, implant failures . Such observations led to a sense of urgency towards the need of redefining bruxism and discriminating between the different bruxism behaviours …”
Section: Discussionmentioning
confidence: 99%
“…While the advantages of this approach may be intuitive to researchers involved in the field, it must be pointed out that it may also influence the future construct of bruxism. For years, bruxism has been generically called into cause as a risk factor for several clinical consequences of dental interest, but the literature has always failed to show a clear‐cut relationship with the purported effects, such as TMDs, occlusal trauma, implant failures . Such observations led to a sense of urgency towards the need of redefining bruxism and discriminating between the different bruxism behaviours …”
Section: Discussionmentioning
confidence: 99%
“…The researchers suggested that bruxism could be considered a marker for chronic stress [41]. Although the impact of bruxism on periodontal health has no consensus [41], it seems to be an aggravating factor for advanced periodontitis [42] even if it has little or no influence on a healthy periodontium or early-stage periodontitis [43].…”
Section: Bruxismmentioning
confidence: 99%
“…Overall, three SR investigated prevalence rates among different populations, seventeen investigated associated factors, six evaluated effects on stomatognathic structures, two evaluated diagnostic accuracy of bruxism assessment tools, and thirteen assessed interventions' effectiveness . Statistical pooling of data using MA was available in 7 studies .…”
Section: Resultsmentioning
confidence: 99%